Karakteristik Industri Sektor Informal Berbasis Pangan di Kabupaten Bandung - Kusumo, Rani Andriani Budi; Mukti, Gema Wibawa; Charina, Anne (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
The micro-food-based industries in Bandung Regency face various challenges that threaten their sustainability. A comprehensive understanding of the characteristics of these industries is essential for formulating policies that support business development, product quality improvement, and market access expansion. This study aims to analyze the characteristics of informal food-based industries in Bandung Regency. The research employed a quantitative design using a survey technique. A total of 115 informal food industry actors were randomly selected as respondents, and data were analyzed descriptively. The findings indicate that most informal business actors are within the productive age group and possess considerable entrepreneurial experience. However, the majority have low levels of education, which limits their managerial and innovative capacities. Most business actors rely on self-financing and source raw materials locally. The main challenges faced include rising raw material costs and declining market demand due to competition and shifting consumer preferences. This study emphasizes the necessity for policy interventions, such as entrepreneurship training, access to financing, and market facilitation to enhance the competitiveness and sustainability of informal food-based industries. Collaborative support between the government and related institutions is essential to overcome existing obstacles and leverage the potential of these industries to contribute to regional economic growth.